2012
DOI: 10.1073/pnas.1117359109
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid dendritic cells control T-cell response to chronic viral infection

Abstract: Infections with persistent viruses are a frequent cause of immunosuppression, autoimmune sequelae, and/or neoplastic disease. Plasmacytoid dendritic cells (pDCs) are innate immune cells that produce type I interferon (IFN-I) and other cytokines in response to virus-derived nucleic acids. Persistent viruses often cause depletion or functional impairment of pDCs, but the role of pDCs in the control of these viruses remains unclear. We used conditional targeting of pDC-specific transcription factor E2-2 to genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
166
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(178 citation statements)
references
References 47 publications
3
166
0
2
Order By: Relevance
“…To test this hypothesis, we took advantage of two different pDC-deficient transgenic mouse strains. For one, DC-E2-2 −/− mice, in which the basic helix-loop-helix transcription factor (E protein) E2-2, essential for pDC development, is deleted in CD11c + cells, constitutively lack pDCs, whereas the cDC lineage is not affected (20). Second, hBDCA-2 DTR mice, that express the high-affinity diphtheria toxin receptor (DTR) under control of the human pDC-specific promoter blood dendritic cell antigen (BDCA)-2, enable efficient inducible pDC depletion by administration of DT (21).…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, we took advantage of two different pDC-deficient transgenic mouse strains. For one, DC-E2-2 −/− mice, in which the basic helix-loop-helix transcription factor (E protein) E2-2, essential for pDC development, is deleted in CD11c + cells, constitutively lack pDCs, whereas the cDC lineage is not affected (20). Second, hBDCA-2 DTR mice, that express the high-affinity diphtheria toxin receptor (DTR) under control of the human pDC-specific promoter blood dendritic cell antigen (BDCA)-2, enable efficient inducible pDC depletion by administration of DT (21).…”
Section: Resultsmentioning
confidence: 99%
“…Although it is well established that DCs can efficiently induce T cell immunity to LCMV, it remains unclear whether DCs are indeed required for T cell priming, acquisition of effector functions, and establishment of memory T cell populations. It was previously shown that selective and constitutive ablation of pDCs had no impact on CD4 and CD8 responses to acute LCMV infection but led to an impaired CD8 response to high-dose infection with the persistent LCMV strain Docile arguing for a critical role of pDCs as IFN producers to control persistent infections (21). Others have shown that cDCs are the main producers of IFN-I in response to acute LCMV infection, and cDC-derived IFN was required to mediate a CTL response to LCMV (19).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Ikaros L/L mice, which lack peripheral pDCs but harbor normal numbers of cDCs, mount efficient B cell-and T cell-specific responses against the influenza virus (18). Other studies have shown that conditional deletion or Ab-mediated depletion of pDCs does not alter the induction of an antiviral CTL response (13,19).…”
mentioning
confidence: 99%